Exploring Indonesian university students’ speaking anxiety in online English medium classes (EMI) - Kusmayanti, Ima Normalia; Hendryanti, Retno; Suwarsono, Litasari Widyastuti (citeus, 2022)
This study investigates the speaking anxiety levels of EFL students enrolled in English medium classes (EMI) in a private university. Factors causing students’ speaking anxiety and potential strategies to reduce the speaking anxiety were also examined. Eighty-nine EMI students from ten undergraduate study programs were the respondents of this study. Data were collected by using Horwitz et al.’s (1986) anxiety survey. Findings showed that EMI students exhibited low-level English-speaking anxiety. The cross-tabulation data demonstrated that students perceived comprehension apprehension as the paramount anxiety factor. To reduce their comprehension apprehension, students prefer their lecturers not to over-react their speaking mistakes and degrade them when they make speaking mistakes. These imply that these findings can be used as consideration for preparatory programs for students and lecturers in EMI classes.